2021
DOI: 10.5937/fme2103563k
|View full text |Cite
|
Sign up to set email alerts
|

Application of discrete wavelet transform to analysis of cutting forces in turning of composites based on aluminium alloys reinforced with Al2O3 fibres

Abstract: This paper presents the results of experimental tests of the turning of an aluminium composite reinforced with Al2O3 fibres. The tests were carried out using three cutting tools with no cutting fluid and in minimum quantity lubrication (MQL) conditions. The cutting forces were measured. For further analyses the main force component was selected. Its mean values and amplitudes were calculated. Then the registered traces were filtered with Daubechies wavelets. Load constancy factors for the filtered off signals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…It is also equally as important to understand the selected machining process and its workings for cost-efficient production. The required surface quality of machined products is of vital importance in determining the viability of the selected machining process [2,3]. This enables engineers to control and manage industrial procedures through research and experimentation for process optimization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also equally as important to understand the selected machining process and its workings for cost-efficient production. The required surface quality of machined products is of vital importance in determining the viability of the selected machining process [2,3]. This enables engineers to control and manage industrial procedures through research and experimentation for process optimization.…”
Section: Introductionmentioning
confidence: 99%
“…A group of researchers investigated minimizing surface roughness and roundness error and maximizing the material removal rate for machinability enhancement of AA6063 T6 Aluminum alloy [3]. They found that FR affects machining at 57.365%, DOC at 25.11%, and CS at 17.35%.…”
Section: Introductionmentioning
confidence: 99%
“…However, they were limited to the ball end mill tool. Karolczak [5] used discrete wavelet transform to analyse the cutting forces in Turning. Zeroudi et al [6].…”
Section: Introductionmentioning
confidence: 99%